2013
DOI: 10.1016/j.agrformet.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven analysis of energy balance closure across FLUXNET research sites: The role of landscape scale heterogeneity

Abstract: The energy balance at most surface-atmosphere flux research sites remains unclosed. The mechanisms underlying the discrepancy between measured energy inputs and outputs across the global FLUXNET tower network are still under debate. Recent reviews have identified exchange processes and turbulent motions at large spatial and temporal scales in heterogeneous landscapes as the primary cause of the lack of energy balance closure at some intensively-researched sites, while unmeasured storage terms cannot be ruled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
351
5
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 500 publications
(402 citation statements)
references
References 203 publications
45
351
5
1
Order By: Relevance
“…The DC values for both sites are closer to the ideal value of 1 than the average DCs found in all published FLUXNET intercomparison studies to date, see Stoy et al (2013) and references therein. Compared to other low-vegetation experiments, the DC values are close to the median (0.9) found by Laubach and Teichmann (1999) reviewing 11 studies over grass or crops, close to the grassland average (0.86) reported by Stoy et al (2013) and comparable to those for three Australian grasslands (0.87, 0.86 and 0.94) given by Leuning et al (2012). To conclude, the surface energy budgets at our sites give no indication of any quality issues beyond what is commonly accepted as inevitable methodical error of the EC technique.…”
Section: J E Hunt Et Al: Carbon Budgets For An Irrigated and An Unmentioning
confidence: 77%
“…The DC values for both sites are closer to the ideal value of 1 than the average DCs found in all published FLUXNET intercomparison studies to date, see Stoy et al (2013) and references therein. Compared to other low-vegetation experiments, the DC values are close to the median (0.9) found by Laubach and Teichmann (1999) reviewing 11 studies over grass or crops, close to the grassland average (0.86) reported by Stoy et al (2013) and comparable to those for three Australian grasslands (0.87, 0.86 and 0.94) given by Leuning et al (2012). To conclude, the surface energy budgets at our sites give no indication of any quality issues beyond what is commonly accepted as inevitable methodical error of the EC technique.…”
Section: J E Hunt Et Al: Carbon Budgets For An Irrigated and An Unmentioning
confidence: 77%
“…Studies on the closure problem of eddy covariance measurements highlight the landscape heterogeneity as a driving factor for the lack of closure (Stoy et al, 2013) but also stress the importance of measurement scales (Foken, 2008). Due to the striking small-scale heterogeneity of soil moisture availability and vegetation cover in Arctic landscapes, measurements of point-scale G and radiative components may not represent the large source area of eddy covariance H and LE.…”
Section: Energy Balance Closure and System Performancementioning
confidence: 99%
“…Low EBCs (60-80 %) were mainly observed at various agricultural sites and bare soil, whereas over forest they were typically higher (80-90 %) (Charuchittipan et al, 2014;Wilson et al, 2002;Foken, 2008a;Panin and Bernhofer, 2008;Stoy et al, 2013). The imbalance usually occurs during day time, particularly around noon, whereas during the night when fluxes are low EBC is often close to unity (Oncley et al, 2007).…”
Section: K Imukova Et Al: Energy Balance Closure On a Winter Wheat mentioning
confidence: 99%
“…This conclusion is supported by Heusinkveld et al (2004); they found a perfect EBC over a homogeneous surface: a desert in Israel. Tsvang et al (1991) and Stoy et al (2013) also concluded that the heterogeneities of the surrounding area are an important factor contributing to the lack of EBC. Several authors (Klaassen and Sogachev, 2006;Friedrich et al, 2000) reported an increase of the turbulent fluxes at forest edges.…”
Section: K Imukova Et Al: Energy Balance Closure On a Winter Wheat mentioning
confidence: 99%